MEMAHAMI TRADISI SPIRITUALITAS PESANTREN (SEBUAH ANALISIS SOSIO-HISTORIS TERHADAP SPIRITUALITAS PESANTREN - Saiful Mujab (Asketik : Jurnal Agama dan Perubahan Sosial, 2017)
This project involves discovering how the spiritually tradition is exist in the pesantren in Indonesia. The goal of this research proves the phenomenon that pesantren and spirituality tradition are strongly linked and connected between each other. Several spiritualities in pesantren are; thoriqoh, tirakat, ijazahan, and others. This article is arranged based on library research and comparing several references by some books, articles and jurnals. Furthermore this research also takes some of experiences of some people who ever study, live, and experience the pesantren tradition in Indonesia (especially in Java). In conclusion, this acticle tries to explore the argumentation historically and socially that Pesantren and spiritualism have strong correlation from the beginning of Islamic spreading in Indonesia. Key word: Pesantren, spiritualism, tarikat